Flexural behavior of reinforced concrete beams under instantaneous loading: Effects of recycled ceramic as cement and aggregates replacement - Samadi, Mostafa; Baghban, Mohammad Hajmohammadian; Kubba, Ziyad; Faridmehr, Iman; Nor Hasanah, Abdul Shukor Lim; Benjeddou, Omrane; Nur Farhayu, Ariffin; Huseien, Ghasan Fahim (MDPI, 2022)
The flexural behavior of five reinforced concrete beams containing recycled ceramic as cement and aggregate replacement subjected to a monotonic static load up to failure was studied. A full-scale, four-point load test was conducted on these beams for 28 days. The experimental results were compared with the conventional concrete as a control specimen. The cross-section and effective span of these beams were (160 × 200 mm) and 2200 mm, respectively. The data recorded during the tests were the ultimate load at failure, steel-reinforcement bar strain, the strain of concrete, cracking history, and mode of failure. The beam containing 100% recycled aggregates displayed an ultimate load of up to 99% of the control beam specimen. In addition, the first crack load was almost similar for both specimens (about 14 kN). The deflection of the beam composed of 100% of the recycled aggregates was reduced by 43% compared to the control specimen. Regardless of the recycled ceramic aggregates ratio, quantities such as service, yield, and ultimate load of the proposed beams exhibited a comparable trend. It was asserted that the ceramic wastes might be of potential use in producing high-performance concrete needed by the structural industry. It might be an effective strategy to decrease the pressure on the environment, thus reducing the amount of natural resources usage.